Situated Perspectives on The Motivational Trajectories of High School Students Learning English in Rural Vietnam - Cuong Pham (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2017)
Despite the growing body of research on the complex and contextually contingent nature of language learning motivation, investigations into the motivation of English language learners in rural areas have remained limited. This study explores the motivational constructions of two high school students learning English in rural Southeast Vietnam from a situated perspective. The students, one female and one male, were in their first year at high school and had relatively low levels of English. Data gathering took approximately one and a half years and was based primarily on interviews drawing on a social practice approach and observations. Findings reveal that students developed diverse motivational trajectories resulting from a synergy of social and idiosyncratic elements pertinent to their own learning conditions, interpersonal relationships, and their agentive appraisals of language affordances and learning opportunities available within and across settings. The longitudinal and situated perspective of this study provides insights into the ways in which students’ appraisals of affordances were shaped and reshaped by on-going interactions with significant others as well as by the sociocultural values permeating their agentive practices.